Pengaruh Penggunaan Aplikasi Quora Sebagai Media Digital dalam Pengembangan Literasi Baca Tulis Bagi Generasi Z - Utari Putri Sriono, Marsa; Prajawinanti, Arin (UPT Perpustakaan Universitas Bengkulu, 2025)
ABSTRACT The impact of the issue of the industry 4.0 phenomenon with the emergence of digital media and technological developments is the Quora application which can be used to develop literacy which emphasizes experience of various subjects based on data, facts and practical knowledge. This research was conducted to find out how the use of the Quora application as digital media influences the development of reading and writing literacy for generation z. This research uses the technology acceptance model theory put forward by Davis and the theory of the national literacy movement put forward by the Ministry of Education and Culture. This research uses a positivism paradigm and a quantitative approach by conducting observations, distributing questionnaires and documentation. The sample used in this research was 100 respondents who were Generation Z users of the Quora application using a purposive sampling technique, namely where the researcher chose the sample based on research knowledge about the sample to be selected. Data was obtained through distributing questionnaires to respondents. Data validity testing was carried out by conducting validity and reliability tests on 30 statement items with valid and reliable results. Meanwhile, power analysis techniques are carried out using normality tests, linearity tests, correlation tests and hypothesis tests. This research uses a simple linear regression analysis technique to test the research hypothesis by conducting a coefficient of determination test and a t test. The results of the R square calculation are 0.529, which shows that there is a correlation between the use of the Quora application as digital media and the development of reading and writing literacy for generation Z, which is 0.471, influenced by other variables outside the research. The research results show that there is a good influence of using the Quora application as digital media in developing reading and writing literacy for generation Z.